Make your own soft toys cut, stitch and sew 25 super-cute friends - Merrett, Rob (London Cico Books, 2013)
This wonderful collection of handmade toys will delight children both young and old. Each toy comes with clear, step-by-step text and beautiful photography and artworks that will guide even a novice stitcher, helping them to produce gorgeous gifts with a charming, handcrafted feel
"Includes pull-out template section" --Cover
First published in 2010 by Cico Books as Sew it, stuff it
Includes index
2
Keywords: Soft toy making -- Patterns; Soft toy making